Spin(7) Instantons on asymptotically conical Calabi-Yau Fourfolds - Papoulias, VE (2022)
The present thesis examines the role of Hermitian Yang-Mills (HYM) connections in Spin(7) instanton moduli spaces over asymptotically conical (AC) Calabi-Yau (CY) fourfolds. The starting point is Lewis' energy estimate: Lewis: if a principal G-bundle P over a closed CY fourfold X8} admits HYM solutions, then all Spin(7) instantons on P are HYM. The question we are interested in is whether this result persists in the AC setting.